Analisis Amanat dalam Seloko Adat Pernikahan di Muaro Jambi - Wahyuni, Suci Sri; Nola, Feni Citra; Salsabila, Andina Nisa (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2024)
Marriage is a sacred thing which is the main gateway for husband and wife in establishing a new relationship and life in the future. In living a household life, of course, not all plans and life run smoothly and smoothly. Therefore, before holding a wedding, it is necessary to be equipped with advice and messages that need to be conveyed, one of which is found in the traditions of Muaro Jambi, namely in traditional wedding rhymes which contain advice and messages for the bride and groom or better known as seloko. The aim of this research is to see the meaning and message conveyed in the rhymes found at traditional wedding ceremonies in Muaro Jambi. Currently, only a few people in Muaro Jambi carry out the traditional wedding rhyme procession at their events. This is because the people of Muaro Jambi do not know the meaning and message of the rhymes delivered at traditional wedding ceremonies. The type of research used in this research is descriptive qualitative. Qualitative research in this study was used to describe the meaning of traditional wedding rhymes in Jambi so that we could find out the message in the rhymes. The data sources in this research are relevant books such as a collection of rhymes and seloko of community wedding customs in Jambi, apart from that, data was also obtained from informants, and several sources from the internet. The data used in this research are the words in traditional wedding rhymes in Jambi which contain mandates. The data collection technique used in this research was carried out by researchers looking for traditional wedding rhymes in Jambi in relevant books, asking traditional leaders in one of the villages in Jambi, and several internet sources. The data analysis technique in this research was carried out by researchers by collecting data first, then reading it, understanding it, then analyzing the meaning and message in the pantun, after knowing the meaning and message the researcher described it in writing. The results of this research are that researchers found 14 data on traditional wedding rhymes that contain mandates in them